One-pot highly enantio- and diastereoselective synthesis of anti,anti vinylic 3-amino-1,2 diols via proline catalyzed sequential alpha-amination/benzoyloxyallylation of aldehydes - Ahuja, Brij Bhushan; Sudalai, Arumugam (RSC Advances, 2015)
The first direct asymmetric synthesis of anti, anti vinylic 3-amino-1,2-diols from aldehydes is described via a one-pot sequential L-proline catalyzed alpha-amination/benzoyloxyallylation protocol. The reaction proceeds with exceptionally high diastereoselectivity (>99%) as can be explained based on the Felkin-Ahn transition state model. Its effectiveness is proven unambiguously by demonstrating a short asymmetric synthesis of D-ribo-phytosphingosine tetraacetate (93% ee).